Nrf2 and autonomic dysregulation in chronic heart failure and hypertension - Wafi, Ahmed M. (Frontiers in Physiology, 2023)
Redox imbalance plays essential role in the pathogenesis of cardiovascular diseases. Chronic heart failure (CHF) and hypertension are associated with central oxidative stress, which is partly mediated by the downregulation of antioxidant enzymes in the central autonomic neurons that regulate sympathetic outflow, resulting in sympathoexcitation. Antioxidant proteins are partially regulated by the transcriptional factor nuclear factor erythroid 2-related factor 2 (Nrf2). Downregulation of Nrf2 is key to disrupting central redox homeostasis and mediating sympathetic nerve activity in the setting of CHF and hypertension. Nrf2, in turn, is regulated by various mechanisms, such as extracellular vesicle-enriched microRNAs derived from several cell types, including heart and skeletal muscle. In this review, we discuss the role of Nrf2 in regulating oxidative stress in the brain and its impact on sympathoexcitation in CHF and hypertension. Importantly, we also discuss